Structure of Isolated Molybdenum(VI) and Molybdenum(IV) Oxide Species on Silica: Periodic and Cluster DFT Studies - Handzlik, Jarosław; Ogonowski, Jan (Journal of physical chemistry. C, 2012)
The structure of monomeric molybdenum oxide species on silica is still a subject under debate. In this work, a large number of advanced silica models are used to study molybdena–silica system with density functional theory. The calculated relative energies of the monooxo and dioxo Mo(VI) species depend on the location of the Mo center on the surface and on the structure of the model. Periodic and cluster calculations employing comparable models of silica give similar results. It is shown that the monooxo Mo(VI) species can be more stable than the dioxo species under dehydrated conditions, provided that the local structure of silica enables preferable 4-fold bonding to the surface. As most locations are favorable for the 2-fold bonded dioxo Mo(VI) species, they should be dominant in the molybdena–silica system, whereas the monooxo Mo(VI) species are predicted to be in minority. The calculated frequencies of the MoO stretching mode for the monooxo Mo(VI) species are generally higher than the frequencies of the symmetric OMoO stretch for the dioxo species, corresponding to the strongest band observed experimentally. The relative energies of the reduced Mo(IV) species on silica are close to the relative energies of the corresponding Mo(VI) precursors.